Globalization and Its Implications on the Growth of Small Medium Enterprises (SMEs) in Western Uganda - Eton, Marus; Ayiga, Natal; Obura, Constant Okello; Mwosi, Fabian; Uwonda Gilbert (International Journal of Research in Management, Economics and Commerce, 2019)
Globalization, characterized by greater economic, political and cultural integration and dependence, has been widely discussed and practiced in the last two decades. The study sought to investigate the implications of globalization on the growth of SMEs in western Uganda, Particularly how globalization affected the productivity and innovation of SMEs in western Uganda. The researcher adopted a cross sectional study design. The Data was collected by the use of structured and closed ended questionnaire. The findings revealed that businesses dealing in imported commodities are fast-growing and register tangible growth results compared to those dealing in locally manufactured commodities. Imported commodities seem not to suit the interests of most Ugandans, perhaps because some are not durable. The study further established that government finds it very difficult to control all the commodities that enter the Ugandan market. The study therefore recommends that Uganda Revenue Authority, under its Anti-Smuggling Unit, should ensure vigilance at border points to reduce the inflow of unauthorized commodities which flood Ugandan market. The Ministry of Trade, Commerce and Industry should step out to protect local firms against competition from foreign producers, particularly those dealing in similar products. Government should lower interest rates through her fiscal and monetary policies to allow SMEs access credit at affordable rates. There is also need to examine the extent to which Uganda’s membership to the East African Community boosts growth of SMEs since all the member countries have almost similar competitive economic advantages.
: a Case of Selected Districts in Western Uganda